Water desalination in Egypt; literature review and assessment - Yasser Elsaie; Sayed Ismail; Hoda Soussa; Mohamed Gado; Ahmed Balah (Ain Shams Engineering Journal, 2023)
The increasing demand for water in urban and industrial areas in arid and semiarid coastal zones has led to the search for alternative nonconventional water resources.. Desalination plants are the most feasible solution to the huge water demand in arid regions, especially in Egypt, with its limited water resources of the Nile River and expected drought due to climate change and upstream dam construction. Many desalination technologies, such as thermal and membrane technologies, are used. Thermal desalination includes multistage flash desalination, multi-effect desalination, and desalination by vapor compression. Membrane desalination involves RO, forward osmosis, and electro dialysis. (RO) desalination plants are the most significant technique for desalinated water in Egypt. However, the treatment of brine wastewater is still a challenging problem. Hypersaline water effluent, as a byproduct of seawater desalination, has a negative impact on the marine ecosystem if it is discharged inadequately. In the past decade, Egypt has launched many large-scale projects along Red Sea and Mediterranean coasts to cope the recent economic growth.In this research a review of taxonomy of many related publications, and comparison has been made between the different seawater desalination techniques to determine the advantages and disadvantages of each of them, as well as to know the best technology that can be used in Egypt. The Egyptian state's plan to address the excessive demand for water resources as a result of the continuous population growth was reviewed by making a strategic plan for 30 years. It was divided into five-year plans, some parts of which have been completed, and the rest of the plan is being completed to present significant comparisons and enable the derivation of informative conclusions.